Noirceur de l’âme, lumière de la Une - Myriam Boucharenc (Criminocorpus)
Détective ? A « stunt » that was not expected and that « does not succeed twice», according to one of its founders, Marius Larique. What is the « recipe » for the exceptional success of this famous « hebdomadaire des faits divers » ? Its launch, however, remained relatively unobtrusive in the press, Détective having mainly built on internal promotional devices, more or less innovative, except for the brilliant idea of the double front page, which turned his readers into human billboards despite them. It seems that it is the intensive exploitation of historical, anthropological and rhetorical affinities between the « fait divers» and the « réclame», which has contributed to making Détective a fundamentally advertising weekly magazine.